Sociodemographic and Environmental Characteristics of Pregnant Women with Chronic Energy Deficiency - Nelly Indrasari; Nurlaila; Roslina; Risneni; Amrina Oktaviana; Eva Berliana (Jurnal Kesehatan, 2026)
Chronic Energy Deficiency (CED) during pregnancy remains a major maternal nutrition problem associated with adverse pregnancy outcomes. This study aimed to describe the sociodemographic and environmental characteristics of pregnant women with CED attending Independent Midwifery Practices in Panjang District, Bandar Lampung City. A descriptive cross-sectional study was conducted in 2024 involving pregnant women identified with CED based on mid-upper arm circumference measurements of <23.5 cm. Total sampling was applied. Data were collected through interviewer-assisted structured questionnaires, anthropometric measurements, and antenatal care record reviews. Descriptive analysis was performed using frequency and percentage distributions. The findings showed that CED occurred across various maternal age groups, including women aged 20–35 years. CED was more common among pregnant women with low educational attainment, informal employment, and low household income. Most respondents also had a history of CED or malnutrition, low body mass index, low protein intake frequency, infrequent consumption of nutrient-dense foods, inadequate antenatal care visits, limited family support, and exposure to secondhand smoke. In conclusion, CED among pregnant women was associated with multiple sociodemographic, nutritional, and environmental characteristics. These findings highlight the importance of strengthening nutritional monitoring, family support, and antenatal care services at the primary health care level to support maternal nutritional status during pregnancy.